1997
DOI: 10.1002/(sici)1096-8628(19970418)74:2<129::aid-ajmg3>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine D2 receptor gene and alcoholism among four aboriginal groups and Han in Taiwan

Abstract: Previous studies examining the putative association between DRD2 TaqI A1 and alcoholism have produced conflicting results. Major critiques of such studies include potential confounding arising from population admixture by inappropriate selection of controls, failure to screen out substance abusers from controls, and the failure to assess the severity of alcoholics. To address these issues, we compared the allelic frequency of two polymorphisms of DRD2, TaqI A and NcoI, among severe alcoholics and their ethnica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 49 publications
0
19
0
1
Order By: Relevance
“…For example, the studies that reported a positive association which showed the frequencies of A1 allele at DRD2 in control is 0.08, 0.11, and 0.07, respectively (Blum et al, 1990;Comings et al, 1991;Neiswanger et al, 1995), all of which are lower than those of the general population in American whites (Barr and Kidd, 1993;Neiswanger et al, 1995). Our study showed that the frequency of A1 allele at DRD2 in nonalcoholic controls was 38.8%, which is very similar to a previous report for Han Chinese population living in Taiwan (Chen et al, 1997). Moreover, the frequency of A1 allele at DRD2 in medial staff controls showed no difference from that in community controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the studies that reported a positive association which showed the frequencies of A1 allele at DRD2 in control is 0.08, 0.11, and 0.07, respectively (Blum et al, 1990;Comings et al, 1991;Neiswanger et al, 1995), all of which are lower than those of the general population in American whites (Barr and Kidd, 1993;Neiswanger et al, 1995). Our study showed that the frequency of A1 allele at DRD2 in nonalcoholic controls was 38.8%, which is very similar to a previous report for Han Chinese population living in Taiwan (Chen et al, 1997). Moreover, the frequency of A1 allele at DRD2 in medial staff controls showed no difference from that in community controls.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported that alcoholism is associated with the TaqI A1 (Arinami et al, 1993;Blum et al, 1991;Chen et al, 1997;Noble et al, 1994;Parsian et al, 1991) or TaqI B1 allele at DRD2 (Blum et al, 1993). However, several other associative studies have reached negative findings (Bolos et al, 1990;Cook et al, 1996;Gejman et al, 1994;Gelernter et al, 1991;Lu et al, 1996).…”
mentioning
confidence: 99%
“…Since then, several groups have replicated the association between alcoholism and this polymorphism Comings et al 1991;Parsian et al 1991;Noble 1994;Hietala et al 1997;Neiswanger et al 1995; Phylogenetic relationships between the predicted ANKK1 kinase and the RIP proteins. The protein sequences were compared by using NJ algorithms (Kumar et al 2001) Neurotox Res (2009) 16:50-59 51 Kono et al 1997;Ishiguro et al 1998;Noble 2003;Foley et al 2004), although other authors have not shown this association (Bolos et al 1990;Gelernter et al 1991;Turner et al 1992;Goldman et al 1997;Arinami et al 1993;Suarez et al 1994;Cruz et al 1995;Sander et al 1995Sander et al , 1999Lu et al 1996;Chen et al 1996Chen et al , 1997Chen et al , 2001Edenberg et al 1998;Lobos and Todd 1998;Gelernter and Kranzler 1999;Waldman et al 1999). This inconsistency was resolved by two recent meta-analyses including a large number of Caucasian alcoholics and controls.…”
Section: Addictive Disordersmentioning
confidence: 97%
“…Since this initial report, there has been an extensive literature examining the relationship between DRD2 and alcohol-related outcomes. While there have been subsequent replications of this genetic association (Blum et al, 1991; Comings et al, 1991; Parsian et al, 1991; Amadeo et al, 1993; Noble et al, 1994; Higuchi et al, 1994; Neiswanger et al, 1995; Hietala et al, 1997; Kono et al, 1997; Ishiguro et al, 1998; Noble, 2003; Foley et al, 2004; Konishi et al, 2004), there have also been numerous studies across a variety of samples, populations, and study designs which fail to find an association between DRD2 and alcohol outcomes (Arinami et al, 1993; Bolos et al, 1990; Chen et al, 1996, 1997, 2001; Cook et al, 1992; Cruz et al, 1995; Edenberg et al, 1998; Gelernter and Kranzler, 1999; Gelernter et al, 1991; Goldman et al, 1992, 1997; Lee et al, 1999; Lobos and Todd, 1998; Lu et al, 1996; Parsian et al, 2000; Sander et al, 1995, 1999; Schwab et al, 1991; Suarez et al, 1994; Turner et al, 1992; Waldman et al, 1999). Critics have proposed that much of this mixed literature resulted from the limitations of early genetic studies including small sample sizes and limited ability to tag all regions of a gene.…”
Section: Introductionmentioning
confidence: 99%